The Environmental Kuznets Curve for Deforestation in Indonesia - Adila, Dara; Nuryartono, Nunung; Oak, Mandar (Economics and Finance in Indonesia, 2021)
This study provides empirical findings on the relationship between deforestation and income in 32 provinces in Indonesia. To enrich the discussion on deforestation, this study investigates the impact of the factors of population, roundwood production, land area, and main crop production on deforestation. The selected main crops in Indonesia are oil palm, coffee, coconut, rubber, and cacao. The results confirm the existence of the EKC relationship between deforestation and income in Indonesia. The study also finds that oil palm production positively affects tree cover loss, but the production of natural rubber has the opposite impact on deforestation.